Incorporation of hydrocolloids into pet food for new applications - Johansson, Joanne (2016)
This thesis investigates how hydrocolloids can be incorporated into pet food meat products to provide novel applications. The possible applications that have been investigated for hydrocolloids are satiety and the production of more sustainable meat products. The research was carried out to improve canned pet food and the processes used to manufacture the product. The main section of the thesis looks at incorporating alginate and pectin solution into a food product which then becomes a gel in a low pH environment. The gel produced in the stomach should produce a satiety effect within the pet. Hydrocolloids used in other studies have been shown to induce satiety in humans. The gel was tested in vitro with a positive result which showed good gelation; however, when tested in vivo, no reduction in food intake was seen. These results may indicate that satiety has different trigger mechanisms in dogs compared to humans. More research is needed to understand whether dogs have the same hormonal responses to satiety as humans. The second application was the use of agar and methylcellulose (MC) to produce a thermally stable gel. The incorporation of this gel structure into a wet meat product would allow the level of meat to be reduced and additional powders to be used as a nutrient component instead. A thermally stable gel also enables the pet food to be processed more efficiently. The gel allows the meat chunks to be cut at high temperatures; therefore, no cooling step is needed in production. Agar and MC produce a strong thermally stable gel at both high and low temperatures. There is evidence that an interpenetrating network is formed in which the molecular ordering and aggregation of the individual polymers appears to be affected by the presence of the second polymer. The use of hydrocolloids for new applications in meat will transform and improve the quality of these products in the future.